Reduced Calcium Signaling Is Associated With Severe Graft-Versus-Host Disease: Results From Preclinical Models and From a Prospective EBMT Study - Riesner, Katarina; Cordes, Steffen; Peczynski, Christophe; Kalupa, Martina; Schwarz, Constanze; Shi, Yu; Mertlitz, Sarah; Mengwasser, Jörg; van der Werf, Steffie; Peric, Zinaida; Koenecke, Christian; Schoemans, Helene; et al. (Frontiers in Immunology, 2020)
Despite its involvement in various immune functions, including the allogeneic activation of T-lymphocytes, the relevance of calcium (Ca²+) for GVHD pathobiology is largely unknown. To elucidate a potential association between Ca²+ and GVHD, we analysed Ca²+-sensing G-protein coupled receptor 6a (GPRC6a) signaling in preclinical GVHD models and conducted a prospective EBMT study on Ca2+ serum levels prior alloSCT including 363 matched sibling allogeneic peripheral blood stem cell transplantations (alloSCTs). In experimental models, we found decreased Gprc6a expression during intestinal GVHD. GPRC6a deficient alloSCT recipients had higher clinical and histopathological GVHD scores leading to increased mortality. As possible underlying mechanism, we found increased antigen presentation potential in GPRC6a-/- alloSCT recipients demonstrated by higher proliferation rates of T-lymphocytes. In patients with low Ca2+ serum levels (<=median 2.2 mmol/l) before alloSCT, we found a higher incidence of acute GVHD grades II-IV (HR=2.3 Cl=1.45-3.85 p=0.0006), severe acute GVHD grades III-IV (HR=3.3 CI=1.59-7.14, p=0.002) and extensive chronic GVHD (HR=2.0 Cl=1.04-3.85 p=0.04). In conclusion, experimental and clinical data suggest an association of reduced Ca2+ signaling with increased severity of GVHD. Future areas of interest include the in depth analysis of involved molecular pathways and the investigation of Ca2+ signaling as a therapeutic target during GVHD.